A study of the linkages between Rolling Budget Forms, Uncertainty and Strategy - Bhimani, A; Sivabalan, P; Soonawalla, K (Elsevier, 2017)
Addressing the dearth of studies on rolling budgets, we investigate how the importance of rolling budgets for various planning, control and evaluation reasons relate to a business unit’s strategy and uncertainty, and report on the variation in these responses when partitioned into quarterly and monthly rolling budget types. We use a survey instrument with responses from 182 rolling budget firms in our investigation. Our findings reveal consistencies as well as deviations between our sub-samples (quarterly and monthly rolling budgets), and the total rolling budget sample. We report that the way rolling budgets relate to uncertainty and strategy in organisations are substantively different for monthly and quarterly rolling budget types, and vary across planning, control and evaluation budget reasons. Our findings show a greater sensitivity between monthly rolling budgets and uncertainty/strategy, and virtually nil relations between quarterly rolling budgets and uncertainty/strategy. We posit that monthly rolling budgets are used in a manner more traditionally associated to rolling budgets in prior studies, while quarterly rolling budgets might be used relatively more symbolically or in response to external pressures such as earnings forecast requirements, and are less sensitive to establish organisational antecedents such as uncertainty/strategy.